Clinical Application of Autologous Adipose Stem Cells in Patients with Multiple Sclerosis: Preliminary Results. (28th September 2016) - Stepien, Adam; Dabrowska, Natalia L.; Maciagowska, Marzena; Macoch, Renata Piusinska; Zolocinska, Aleksandra; Mazur, Slawomir; Siennicka, Katarzyna; Frankowska, Emilia; Kidzinski, Rafał; Chalimoniuk, Małgorzata; Pojda, Zygmunt
Abstract : The clinical outcome of autologous adipose stem cell (ASC) treatment of patients with multiple sclerosis (MS) was investigated following one year of observation. Methods . The clinical and MRI outcomes of 16 ASC-treated patients with RRMS and SPMS are reported after a one-year follow-up period. Results. At 18 months of follow-up, some patients showed "enticing" improvements on some exploratory efficacy measures, although a significant benefit was not observed for any measure across the entire group. Neither the progression of disability nor relapses were observed in any cases. In four patients, we found new gadolinium+ (Gd+) lesions on MRI. Our results indicate that ASC therapy is safe and does not produce any substantial side effects. Disease progression-free survival (PFS) of 18 months was seen in all patients with RRMS and SPMS. In these patients, EDSS scores did not progress above baseline scores. Gd-enhancing lesions were observed in two cases with RRMS, but these patients did not exhibit changes in EDSS score. Conclusion . Intrathecal treatment with ASCs is an attractive form of therapy for patients with MS but should be reserved for cases with aggressive disease progression, for cases that are still in the inflammatory phase, and for the malignant form.